2023
DOI: 10.1002/hed.27554
|View full text |Cite
|
Sign up to set email alerts
|

An unexpected complication of hypoglossal schwannoma surgery: Cerebrospinal fluid leakage—A case report and literature review

Orhan Asya,
Ömer Faruk Kuyumcu,
Yavuz Gündoğdu

Abstract: BackgroundExtracranial hypoglossal schwannoma is a rare tumor primarily treated with surgical excision. This article aims to highlight the potential for unexpected complications intraoperatively, such as cerebrospinal fluid leakage from skullbase to neck.MethodsA previously healthy 23‐year‐old male presented with tongue numbness. Magnetic resonance imaging revealed a 17 × 20 mm nodular lesion adjacent to the cervical segment of the internal carotid artery. Surgical excision was scheduled due to suspicion of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 15 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Schwannomas are rare benign neoplasms, originating from myelin-producing Schwann's cells, with predilection for sensory nerves (1,(3)(4)(5). They represent less than 1% of the neoplasms seen in the head and neck region.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Schwannomas are rare benign neoplasms, originating from myelin-producing Schwann's cells, with predilection for sensory nerves (1,(3)(4)(5). They represent less than 1% of the neoplasms seen in the head and neck region.…”
Section: Discussionmentioning
confidence: 99%
“…The primary objective is the complete tumor resection with meticulous dissection from the nerve fascicles. Studies have shown that intracapsular enucleation preserves nerve function without recurrence (5,23). En bloc resection of the nerve has been suggested to reduce the risk of recurrence and potential for sarcomatous transformation (24).…”
Section: Histopathological Examination Under Microscope A) Encapsulat...mentioning
confidence: 99%
See 3 more Smart Citations